Degradation of Anti-Inflammatory Drugs in Synthetic Wastewater by Solar Photocatalysis - Marwan Al-Jemeli (MDPI AG, 2021)
Due to the high number of anti-inflammatory drugs (AIMDs) used by the public health sector in Iraq and distributed all over the country and due to their toxicity, there is a need for an environmental-friendly technique to degrade any wasted (AIMD) present in aquatic ecosystem. The degradation of diclofenac sodium (DCF), ibuprofen (IBN), and mefenamic acid (MFA) in synthetic hospital wastewater were investigated utilizing locally-made Cu-coated TiO2 nanoparticles in a solar-irradiated reactor. Different key variables were studied for their effects on process efficiency, such as loadings of catalyst (C CU-TiO2 = 100–500 mg/L), AIMDs (100 µg/L), pH (4–9), and hydrogen peroxide (CH2O2 = 200–800 mg/L). The results revealed that degradation percentages of 96.5, 94.2, and 82.3%, were obtained for DCF, IBN, and MFA, respectively, using our Cu-coated TiO2 catalyst within 65 min at pH = 9, while other parameters were C CU-TiO2 = 300 mg/L, and CH2O2 = 400 mg/L. The experimental results revealed coupling photocatalysis with solar irradiation as a clean energy source could be utilized for the degradation of toxic pollutants in surface water.